The importance of daily routines in the lives of adolescent learners (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article discusses the aspects of the correct establishment of the daily routine in the daily life of adolescents, how students adhere to the daily routine, which largely depends on the educational potential and level of responsibility of parents.